2021
DOI: 10.1186/s43042-021-00135-2
|View full text |Cite
|
Sign up to set email alerts
|

The association of apolipoprotein-E (APOE) gene polymorphisms with coronary artery disease: a systematic review and meta-analysis

Abstract: Background Numerous studies have investigated the role of apolipoprotein E (APOE) polymorphisms in coronary artery disease (CAD), but some controversies exist regarding the outcomes as the results were not consistent and remain uncertain. Therefore, the present meta-analysis was conducted to evaluate the association of APOE polymorphisms with coronary artery disease. Methods All the relevant studies published in English language till August 2020 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…The levels of HDL were decreased significantly in all genotypes, confirming its association with APOE polymorphism. A study carried out by Ashiq et al, 2021 [ 49 ], showed that E4/4 is the reason for cardiac disease in diabetics while allele 2 is cardioprotective, which is different from the present study results. E2/3 and 4/4 were both found to be associated with IHD in addition to stroke in subjects with diabetes.…”
Section: Discussioncontrasting
confidence: 99%
“…The levels of HDL were decreased significantly in all genotypes, confirming its association with APOE polymorphism. A study carried out by Ashiq et al, 2021 [ 49 ], showed that E4/4 is the reason for cardiac disease in diabetics while allele 2 is cardioprotective, which is different from the present study results. E2/3 and 4/4 were both found to be associated with IHD in addition to stroke in subjects with diabetes.…”
Section: Discussioncontrasting
confidence: 99%
“…The finding of the Ɛ4 allele as a risk of CAD is in agreement with the meta-analysis conducted previously. 16,[34][35][36][37] Ɛ4 allele increases the cholesterol level by enhancing the transfer of cholesterol ester from HDL to TG-rich lipoproteins which promotes the hepatic remnant clearance by APOE receptors and decreases LDLR. 38 Furthermore, the meta-analysis by Xu et al 35 reported that Ɛ4 allele had a 46% higher risk of CAD (OR = 1.46, 95% CI = 1.28-1.66).…”
Section: Discussionmentioning
confidence: 99%
“…This could cause delayed LDL clearance and increased serum LDL level [ 67 ], increasing the chances for LDL deposition in the coronary intima, thus making the apo-E2 a likely risk factor for CHD. A recent meta-analysis of candidate gene studies seemed to support this theory since rs7412*T was associated with a 1.38-times-higher CHD risk (95% CI: 1.18–1.62) [ 68 ]. In contrast, our meta-analysis of GWAS publications yielded the opposite result, wherein the rs7412*T conferred a protective effect against CHD (OR: 0.93, 95% CI: 0.91–0.96) ( Table S2 ).…”
Section: Discussion and Narrative Synthesismentioning
confidence: 99%